Acute management and outcomes of iatrogenic dissections during cerebral angiography. (15th April 2016) - Groves, Andrew P; Kansagra, Akash P; Cross, DeWitte T; Moran, Christopher J; Derdeyn, Colin P
Abstract : Background and purpose: Iatrogenic dissection is a known complication of cerebral angiography, but the clinical outcomes and optimal treatment of these patients is not well established. We sought to review our experience with cerebral angiography to determine the incidence of iatrogenic dissections along with clinical outcomes associated with a generally conservative treatment strategy. Materials and methods: We retrospectively reviewed clinical records for all patients that underwent cerebral angiography between March 2002 and May 2015. Demographic information, angiography reports, follow-up CT and MRI reports, and follow-up clinical notes were reviewed. Results: 17 418 cerebral angiograms were performed during the review period, including 13 485 diagnostic angiograms and 3933 endovascular interventional procedures. 68 iatrogenic dissections were identified, for a per procedure incidence of 0.39%. The vertebral artery was the most commonly dissected vessel (49/68, 72%). 67 of 68 cases (98.5%) were managed conservatively with either no treatment or medical therapy alone. There were two adverse events potentially attributable to the dissections, only one of which was symptomatic. Conclusions: Iatrogenic dissections occur infrequently during cerebral angiography. When dissections do occur, most cases can be safely managed without further intervention in the acute setting.